1977
DOI: 10.1111/j.1365-2133.1977.tb07131.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal epithelial hyperplasia of the oral mucosa.

Abstract: Two negro siblings with focal epithelial hyperplasia of the oral mucosa are described. A review of the literature is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Other reports have since appeared and it is now clear that the disease occurs in certain native ethnic groups such as Blacks, Esquimos, South American Indians and rarely in caucasians (12,14). The disease occurs primarily in groups with a poor social and economic status and affects mainly children and young adults with frequent manifestation within the same family.…”
Section: Discussionmentioning
confidence: 97%
“…Other reports have since appeared and it is now clear that the disease occurs in certain native ethnic groups such as Blacks, Esquimos, South American Indians and rarely in caucasians (12,14). The disease occurs primarily in groups with a poor social and economic status and affects mainly children and young adults with frequent manifestation within the same family.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple, symptomless, papillomatous-like swellings was found on the lower and upper lips, buccal mucosa, gingiva and the borders of the tongue of a 12-year-old black boy, the hard palate was involved as well. Two years later, Starink TM et al reported two MEH cases involving gingiva of a 9-year-old girl and a 4-year-old boy, respectively [ 12 ]. In 1982, Lutzner M et al described MEH lesions on the gingiva of a 10-year-old boy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology has not been determined; a virus (Praetorius-Clausen & Willis 1971, Hanks et al 1972, van Wyk et al 1977 and heredity (Gomez et al 1969, Schock 1969, Buchner 1978 have been suggested as etiologic factors. While viral particles of the papova virus group have been demonstrated in some human cases (Hanks et al 1972, Praetorius-Clausen 1972, van Wyk et al 1977, not all investigators have been able to demonstrate them (Orfanos et al 1974, 03OO-9777/79/040213-ll$02.50/0 Buchner et al 1975, Starink & Woerdeman 1977. Viral particles have also been demonstrated in chimpanzee lesions (Hollander & van Noord 1972, Tate et al 1973).…”
Section: Focalmentioning
confidence: 99%